A new quantitative image-based method for evaluation of bony temporal hollowing in metopic synostosis. Issue 6 (1st November 2016) - Hagmarker, Linn; Söfteland, Madiha Bhatti; Maltese, Giovanni; Tarnow, Peter; Wikberg, Emma; Kölby, Lars; Bernhardt, Peter
Abstract: Objective: Premature craniosynostosis is a congenital disorder causing a skull deformity. For both functional and cosmetic reasons, the deformity is surgically treated with a cranioplasty before the age of 1 year. Temporal hollowing is a common and undesirable remaining deformity after cranioplasty for metopic synostosis. The most common method to determine the degree of temporal hollowing is subjective judgement of the temporal region. The aim of the present project was to develop a quantitative semi-automatic computer tool for objective measurement of bony temporal hollowing. Methods: Using MATLAB, a tool was developed to segment computed tomography images, defining the outermost contour. The images were dorsally limited to the widest point of the head. In each case, a sex- and age-matched control was identified and the contours compared. The bony temporal hollowing of the cases was calculated. Results: The intra-user coefficient of variation (CV) was 5.0% (95% CI = 4.2%–6.2%) and the inter-user CV was 3.0% (95% CI = 2.1%–8.6%). For clinical testing purposes, the tool was used in 14 patients, seven of whom had been operated on with a spring-assisted cranioplasty and seven with a cranioplasty using a bone graft. Conclusions: In summary, this study presents a new tool for objective measurement of the surgical result after cranioplasty for metopic synostosis.